1994
DOI: 10.1175/1520-0477(1994)075<2097:llsfdw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lead Seasonal Forecasts—Where Do We Stand?

Abstract: The National Weather Service intends to begin routinely issuing long-lead forecasts of 3-month mean U. S. temperature and precipitation by the beginning of 1995. The ability to produce useful forecasts for certain seasons and regions at projection times of up to 1 yr is attributed to advances in data observing and processing, computercapability, and physical understanding-particularly, for tropical ocean-atmosphere phenomena. Because much of the skill of the forecasts comes from anomalies of tropical SST relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
109
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(114 citation statements)
references
References 51 publications
4
109
0
1
Order By: Relevance
“…The quality of predictions of the ENSO state has improved over the decades beginning with the first ones in the 1980s based on simplified coupled ocean-atmosphere physics (e.g., Cane et al 1986) and advancing into the twenty-first century with comprehensive coupled general circulation models and sophisticated data assimilation techniques to set the initial conditions. Evaluations of the skill of ENSO predictions have been presented periodically along this long developmental path (e.g., Barnston et al 1994Barnston et al , 1999Barnston et al , 2012Tippett and Barnston 2008;Tippett et al 2012;L'Heureux et al 2016;Tippett et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The quality of predictions of the ENSO state has improved over the decades beginning with the first ones in the 1980s based on simplified coupled ocean-atmosphere physics (e.g., Cane et al 1986) and advancing into the twenty-first century with comprehensive coupled general circulation models and sophisticated data assimilation techniques to set the initial conditions. Evaluations of the skill of ENSO predictions have been presented periodically along this long developmental path (e.g., Barnston et al 1994Barnston et al , 1999Barnston et al , 2012Tippett and Barnston 2008;Tippett et al 2012;L'Heureux et al 2016;Tippett et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Imperative for a comparison of forecast performance is the consistency in predictand and a sufficiently long prediction period common to the two approaches. In such a comparison for the seasonal forecasting of equatorial Pacific SST, Barnston et al (1994) found that numerical modelling did not surpass the performance of empirically based prediction. Half a decade later, Barnston et al (1999) confirmed the earlier assessment and expressed reservation on whether numerical modelling would ever outperform empirical methods, consistent with perceptions conveyed by other authors (Webster et al, 1998;Anderson et al, 1999;Bamzai and Shukla, 1999;Lorenz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Prediction throughout the tropics on the basis of the empirical diagnostics and numerical modelling has been appraised in a sequence of reviews over the past decades (Hastenrath, 1985(Hastenrath, , 1986(Hastenrath, , 1990(Hastenrath, , 1995a(Hastenrath, ,b, 2002(Hastenrath, , 2006aBarnston et al, 1994Barnston et al, , 1999Palmer and Anderson, 1994;Carson, 1998;Latif et al, 1998, Anderson et al, 1999Nobre et al, 2006). Comparison of performance of the empirical and numerical modelling approaches is called for.…”
Section: Introductionmentioning
confidence: 99%
“…The pervasiveness of the ENSO relationship with Indian climate and the prospect of forecasting ENSO events with useful skill at longer lead-time (Barnston et al, 1994;Latif et al, 1994;Chen et al, 1995) suggests an unprecedented opportunity to predict Indian foodgrain production. Where an influence of ENSO on foodgrain production can be demonstrated, the ENSO prediction may be used either to mitigate the impacts of adverse conditions or to take advantage of favourable conditions.…”
Section: Introductionmentioning
confidence: 99%